2004
DOI: 10.1161/01.str.0000112972.09096.65
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recanalization on Outcome in Dural Sinus Thrombosis

Abstract: Background and Purpose-Recanalization in dural sinus thrombosis (DST) has been observed previously; however, systematic prospective data are lacking. The influence of recanalization on DST outcome has not yet been thoroughly evaluated. Methods-Thirty-seven consecutive patients with DST were prospectively examined. Neurological deficits were graded with the National Institutes of Health Stroke Scale (NIHSS) on hospital admission and discharge. Functional outcome was assessed with the modified Rankin Scale (mRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 24 publications
6
80
0
8
Order By: Relevance
“…18 Furthermore, no significant differences in relapses or outcome were found in those with incomplete or no recanalization. 19,20 In our study, baseline imaging features such as location and thrombus load were not associated with thrombotic recurrence.…”
Section: Discussionmentioning
confidence: 43%
“…18 Furthermore, no significant differences in relapses or outcome were found in those with incomplete or no recanalization. 19,20 In our study, baseline imaging features such as location and thrombus load were not associated with thrombotic recurrence.…”
Section: Discussionmentioning
confidence: 43%
“…Partial or complete recanalization rates for CVT ranged from 47% to 100% with anticoagulation alone. 110,178,[192][193][194] Unfortunately, most studies reporting partial or complete recanalization at 3 to 6 months have a small sample size. When 4 studies that included 114 CVT patients were combined, partial or complete recanalization at 3 to 6 months was observed in 94 (82.5%).…”
Section: Other Treatmentsmentioning
confidence: 99%
“…When 4 studies that included 114 CVT patients were combined, partial or complete recanalization at 3 to 6 months was observed in 94 (82.5%). 110,178,192,193 Recanalization rates may be higher for patients who receive thrombolytic therapy. 14 In general, thrombolytic therapy is used if clinical deterioration continues despite anticoagulation or if a patient has elevated intracranial pressure that evolves despite other management approaches.…”
Section: Other Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, CVST had been associated with a dismal prognosis and high mortality rate, reaching 30-50%. 5,54 Recent studies, 6,32,37,64,65,68 and especially the ISCVT study, performed in the era of modern neuroimaging, LMWH administration, and endovascular intervention, reported much lower mortality rates (8-14%) and significantly better outcome. A meta-analysis of 19 studies conducted by Dentali et al 22 showed that the mortality rate during the perihospitalization period was about 5.6%, while at the end of the follow-up period, this percentage increased to 9.4%.…”
Section: Outcome and Prognosismentioning
confidence: 99%